Soil mites (Acari, Mesostigmata) from Szczeliniec Wielki in the Stołowe Mountains National Park (SW Poland) - Kamczyc, Jacek; Gwiazdowicz, Dariusz (Biological Letters, 2010)
The species composition of mesostigmatid mites in the soil and leaf litter was studied on the Szczeliniec Wielki plateau, which is spatially isolated from similar rocky habitats. A total of 1080 soil samples were taken from June 2004 to September 2005. The samples, including the organic horizon from the herb layer and litter from rock cracks, were collected using steel cylinders (area 40 cm2, depth 0-10 cm). They were generally dominated by Gamasellus montanus, Veigaia nemorensis, and Leptogamasus cristulifer. Rhodacaridae, Parasitidae and Veigaiidae were the most numerously represented families as regards to individuals. Among the 55 recorded mesostigmatid species, 13 species were new to the fauna of the Stołowe National Park. Thus the soil mesostigmatid fauna of the Szczeliniec Wielki plateau is generally poor and at an early stage of succession.